Children’s exposure to herbicides in Jalisco, Mexico—a public health concern perspective - de Jesús Lozano-Kasten, Felipe; Peregrina-Lucano, Alejandro Aarón; Fausto-Guerra, Josefina; Velazco-Sandoval, Norma Guadalupe Ruiz; Flores-Rodríguez, Daniel; Guzmán-Torres, Horacio (Frontiers in Public Health, 2025)
This perspective article examines public health concerns related to herbicide exposure among children living in an agricultural and fishing village on the shores of Lake Chapala in Jalisco, Mexico. The discussion draws on published research comprising four pesticide exposure assessments conducted on children aged 0–14 years between 2016 and 2018. These assessments involved the collection of first-morning urine samples, which were analyzed using high-performance liquid chromatography coupled with tandem mass spectrometry (HPLC-MS/MS). The findings are as follows: November 2016 (n = 347; 24.2% positive; 7 herbicides detected), October 2017 (n = 187; 86.6% positive; 6 herbicides detected), May 2018 (n = 347; 52.2% positive; 4 herbicides detected), and October 2018 (n = 347; 12% positive; 4 herbicides detected). A total of three herbicides—glyphosate, 2,4-D (2,4-dichlorophenoxyacetic acid), and molinate—were detected in each of the four assessments. These results may represent the first evidence of persistent herbicide exposure in children in the Lake Chapala region. Further epidemiological studies are required to deepen the understanding of these findings.